2020
DOI: 10.1007/s10900-020-00859-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study on Awareness and Knowledge of COVID-19 Among Senior pharmacy Students

Abstract: Extraordinary actions have been implemented in an effort to control the rapid spread of the ongoing COVID-19 epidemic in Egypt. People's adherence to control measures is influenced by their knowledge, attitudes and practices towards the disease. Therefore, in the present study we assessed pharmacy senior students' knowledge, attitudes and practices towards the COVID-19 pandemic. An online questionnaire was created and it consisted of 12 questions testing their knowledge about COVID-19 clinical characteristics,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
81
4
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 21 publications
20
81
4
15
Order By: Relevance
“…This present study showed that 71.22% of the students wore masks, gloves, and goggles. Only about 50% of the participants were willing to wear face masks in a previous study [ 13 ]. The difference may be due to the rapid depletion of masks since the coronavirus pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This present study showed that 71.22% of the students wore masks, gloves, and goggles. Only about 50% of the participants were willing to wear face masks in a previous study [ 13 ]. The difference may be due to the rapid depletion of masks since the coronavirus pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between students’ knowledge, attitudes, and practice shows that sufficient knowledge and positive attitudes are affecting their actions against COVID-19. Knowledge is a prerequisite for establishing positive attitudes and promoting positive behaviors [ 13 ], although eHealth literacy can promote the acquisition and application of online health information to adopt a positive attitude and conduct health-promoting activities. Therefore, for nurse undergraduates, it is crucial to provide emergency disease training, increase eHealth literacy courses, and improve the curriculum with courses such as epidemiology and new emerging diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS Corona viruses in 2002 and 2003 triggered extreme Severe acute respiratory syndrome outbreaks in Guangdong Province, China (Modenese and Gobba, 2020). In the same way, MERS Cov viruses were responsible for Middle East Respiratory Syndrome outbreaks in 2012 which happened primarily in the Middle East Countries (Hamza et al, 2020;Gambhir, 2020). Following their origin, The SARS Cov 2 viruses have infected more than 5.1 million people residing over 188 countries and territories (Angelantonio et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…The two severe forms of Corona viruses are zoonotic in origin and cause fatal illness in affected people (Hamza et al, 2020;Gambhir, 2020). SARS Corona viruses in 2002 and 2003 triggered extreme Severe acute respiratory syndrome outbreaks in Guangdong Province, China (Modenese and Gobba, 2020).…”
Section: Introductionmentioning
confidence: 99%